PENGARUH LIKUIDITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDENDAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Putu Weda Kartini Putri (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2016)
This study aims to determine the effect of Dividend Policy as mediation Liquidity and Growth Company to Corporate Value. The population of this research is a Manufacturing company in BEI 2010-2013. The sample selectionis done by using purposive sampling method included in the sampling nonprobability sampling technique. The sample was selected on the basis of suitability characteristics of the sample with the sample criteria with criteria that company during the observation period 2010-2013 year fixed or not out of the list of Manufacturing Index, which amounts to 38 companies. The research data is secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id) and ICMD 2010-2013. Testing hypotheses of the study used path analysis technique with an application tool SPSS 17th version of the results show ed that: 1) Liquidity significant negative effecton Dividend Policy, 2) Company Growth negative and significant impacton the profitability, 3) Liquidity significant positive effect on value companies, 4) Growth company significant negative effecton the value of the Company, 5) Dividend policy significant positive effecton firm value, 6) Dividend policy is not able to mediate between Liquidity Rated company. 7) Dividend policy is not able to mediate between the growth of the Company's Corporate Value.